2018
DOI: 10.1177/1759091418812587
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein Trafficking in Parkinson’s Disease: Insights From Fly and Mouse Models

Abstract: Protein aggregation and accumulation are common pathological hallmarks in neurodegenerative diseases. To efficiently clear and eliminate such aggregation becomes an important cellular strategy for cell survival. Lewy bodies inclusion and aggregation of α-Synuclein (α-Syn) during the pathogenesis of Parkinson’s disease (PD) serve as a good example and are potentially linked to other pathological PD features such as progressive dopaminergic neuron cell death, behavioral defects, and nonmotor symptoms like anosmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 182 publications
1
7
0
Order By: Relevance
“…GO enrichment (Eden et al, 2009) shows that a-synuclein toxicity enriches ubiquitination of proteins associated with gene expression, protein synthesis, and metabolic processes relative to the total ubiquitylome (Table S3). These results are consistent with previous characterizations of processes disrupted by a-synuclein-associated ER and cellular stress (Cheng et al, 2018;Eisbach and Outeiro, 2013;Fernandes et al, 2016;Jiang et al, 2010;Lautenschl€ ager et al, 2017;Mercado et al, 2013;Zambon et al, 2019). Further analysis of ubiquitin linkage abundances (determined by comparison of diagnostic GG-K peptide abundances between samples) revealed that induction of a-synuclein toxicity increases the amount of K6-, K11-, K33-, K48-, and K63-linked ubiquitin chains relative to WT controls ( Figure 5D).…”
Section: Confocal Immunofluorescence Microscopy To Map Nab2-dependentsupporting
confidence: 93%
“…GO enrichment (Eden et al, 2009) shows that a-synuclein toxicity enriches ubiquitination of proteins associated with gene expression, protein synthesis, and metabolic processes relative to the total ubiquitylome (Table S3). These results are consistent with previous characterizations of processes disrupted by a-synuclein-associated ER and cellular stress (Cheng et al, 2018;Eisbach and Outeiro, 2013;Fernandes et al, 2016;Jiang et al, 2010;Lautenschl€ ager et al, 2017;Mercado et al, 2013;Zambon et al, 2019). Further analysis of ubiquitin linkage abundances (determined by comparison of diagnostic GG-K peptide abundances between samples) revealed that induction of a-synuclein toxicity increases the amount of K6-, K11-, K33-, K48-, and K63-linked ubiquitin chains relative to WT controls ( Figure 5D).…”
Section: Confocal Immunofluorescence Microscopy To Map Nab2-dependentsupporting
confidence: 93%
“…It is proposed that oxidative stress in dopaminergic neurons prompted the activation of the p38 MAPK and c-Jun N-terminal kinase (JNK) signaling pathways that have linked to neuronal apoptosis in several models of PD (Oh et al, 2011;Sabens Liedhegner et al, 2011;Bohush et al, 2018). p38-MAPK activation has also been reported to contribute to mitophagy, a fundamental mechanism underlying α-synuclein accumulation associated with PD (Cheng et al, 2018).…”
Section: Trps Involvement In Pain Alzheimer's and Parkinson's Diseasesmentioning
confidence: 99%
“…These results are consistent with previous characterizations of processes disrupted by α-synuclein-associated ER and cellular stress. [39][40][41][42][43][44][45] Further analysis of ubiquitin linkage abundances (determined by comparison of diagnostic GG-K peptide abundances between samples) revealed that induction of α-synuclein toxicity increases the amount of K6, K11, K33, K48, and K63 linked ubiquitin chains relative to wild-type controls ( Figure 5D). Strikingly, K63 linkages, which primarily trigger endocytosis and lysosomal degradation of plasma membrane proteins, 46 are enriched 8-fold relative to the wild-type sample.…”
Section: Ubiquitin Enrichment-coupled Proteomic Analyses For Assessmementioning
confidence: 99%